MicroRNA‐122 associates with serum apolipoprotein B but not liver fibrosis markers in CHC genotype 1 infection. Issue 10 (11th May 2015) - Lee, Tzu‐Hao; Matta, Bassem; King, Bernard D.; Hodges, Michael R.; Tillmann, Hans L.; Patel, Keyur
<x xml:space="preserve">Abstract</x> miR‐122 is the predominant liver miRNA that regulates hepatic lipid metabolism and inflammation. Hepatitis C virus (HCV) modulates host intracellular lipid metabolism. HCV stability and propagation also depend on an interaction between virus and miR‐122. Our aims were to examine the associations between miR‐122, apolipoproteins, and serum makers of fibrosis in chronic hepatitis C (CHC) patients. We evaluated baseline sera from 36 CHC genotype 1 patients who completed the Phase IIa study of miravirsen (LNA oligonucleotide targeting miR‐122). Samples were assessed for liver transaminases, IL 28B genotype, IP‐10, and lipid profiles. The noninvasive markers of liver fibrosis, APRI, and FIB‐4, were calculated using standard formulae. miR‐122 levels were measured using RT‐PCR and expressed as fold‐change compared to normal healthy controls. CHC patients were mostly male (61%) with mean age 47.5 ± 11.6 years. Patients with higher ApoB (ApoB/ULN ≥ 0.5) has significantly lower miR‐122 levels in compared to patients with lower ApoB (ApoB/ULN < 0.5). (8.28 ± 6.23 vs. 16.28 ± 13.71; P = 0.02). There were no similar associations between miR‐122 and ApoA‐1 or between HCV RNA and lipoproteins. There were no differences in miR‐122 levels between patients with different stages of fibrosis determined by APRI or FIB‐4. Patients with lower ApoB had higher serum miR‐122 levels. However, we cannot identify significant association between miR‐122, ApoA‐1, or fibrosis markers in this small cohort of CHC genotype 1 patients. The mechanism of HCV dyslipidemia is complex and could partly relate to the effect of miR‐122 on lipid metabolism which requires further evaluation in a larger study. J. Med. Virol. 87:1722–1726, 2015. © 2015 Wiley Periodicals, Inc.